Trade-offs between carbon sequestration, landscape aesthetics and biodiversity in a cost-benefit analysis of land use options in Norway - Endre Kildal Iversen; Kristine M. Grimsrud; Henrik Lindhjem; Jette Bredahl Jacobsen (Statistics Norway, Research Department, 2019)
Norway is considering a national afforestation program for greenhouse gas (GHG) sequestration on recently abandoned semi-natural pastureland. However, the program may have negative impacts on landscape aesthetics and biodiversity. We conducted a national choice experiment survey to estimate non-market benefits of the afforestation program, compared to an alternative program of recovering pastures and the status quo of natural reforestation. Combining the preference data with secondary data on costs, we derive the social net return on land use alternatives. We find that restoring half of the abandoned pastures for grazing yields the highest net present value. Rural households closer to abandoned pastures are the largest beneficiaries of this policy due to the value they place on pastures and their disutility of natural reforestation. Their willingness to pay (WTP) for recovering pastures is more than three times that of urban households, while non-use values derived from carbon sequestration and biodiversity seem more constant across space. The net present value of all land use alternatives are still positive when limiting the aggregation of WTP to rural households, and when allowing for the presence of substantial hypothetical bias in benefit estimates and for cost increases. Results indicate that landscape and biodiversity values are substantial and should be considered when designing agricultural and climate policies.
Keywords: Q18; Q15; Q51; Q54; Q57; 330; Climate forest; biodiversity; pastures; discrete choice experiment; nonuse values; cost-benefit analysis